Women in chicken business: Veterinarian Anande Munisi's story - International Livestock Research Institute (International Livestock Research Institute, 2022)
The Women in Business Project is developing, promoting, and testing women-led chicken businesses in Ethiopia and Tanzania. This work will bring about the economic empowerment of young women and improve the food and nutrition security of their households through chicken businesses. This video features Anande Munisi, and her experience as one of the young women veterinarian graduates in the Women in Business project to bring improved chicken breeds, inputs, advice and market outlets to women chicken farmers in Tanzania.